Sex and Adolescent Ethanol Exposure Influence Pavlovian Conditioned Approach. (13th March 2017) - Madayag, Aric C.; Stringfield, Sierra J.; Reissner, Kathryn J.; Boettiger, Charlotte A.; Robinson, Donita L.
Abstract : Background: Alcohol use among adolescents is widespread and a growing concern due to long‐term behavioral deficits, including altered Pavlovian behavior, that potentially contribute to addiction vulnerability. We tested the hypothesis that adolescent intermittent ethanol (AIE) exposure alters Pavlovian behavior in males and females as measured by a shift from goal‐tracking to sign‐tracking. Additionally, we investigated GLT‐1, an astrocytic glutamate transporter, as a potential contributor to a sign‐tracking phenotype. Methods: Male and female Sprague‐Dawley rats were exposed to AIE (5 g/kg, intragastric) or water intermittently 2 days on and 2 days off from postnatal day (P) 25 to 54. Around P70, animals began 20 daily sessions of Pavlovian conditioned approach (PCA), where they learned that a cue predicted noncontingent reward delivery. Lever pressing indicated interaction with the cue, or sign‐tracking, and receptacle entries indicated approach to the reward delivery location, or goal‐tracking. To test for effects of AIE on nucleus accumbens (NAcc) excitatory signaling, we isolated membrane subfractions and measured protein levels of the glutamate transporter GLT‐1 after animals completed behavior as a measure of glutamate homeostasis. Results: Females exhibited elevated sign‐tracking compared to males with significantly more lever presses, faster latency to first lever press, and greater probability to lever press in a trial. AIE significantly increased lever pressing while blunting goal‐tracking, as indicated by fewer cue‐evoked receptacle entries, slower latency to receptacle entry, and lower probability to enter the receptacle in a trial. No significant sex‐by‐exposure interactions were observed in sign‐ or goal‐tracking metrics. Moreover, we found no significant effects of sex or exposure on membrane GLT‐1 expression in the NAcc. Conclusions: Females exhibited enhanced sign‐tracking compared to males, while AIE decreased goal‐tracking compared to control exposure. Our findings support the hypothesis that adolescent binge ethanol can shift conditioned behavior from goal‐ to cue‐directed in PCA, especially in females. Abstract : Male and female Sprague–Dawley rats were exposed to adolescent intermittent ethanol (AIE), and then trained on Pavlovian conditioned approach in adulthood. Adolescent binge‐level ethanol (EtOH) produced similar blood EtOH concentration in males and females. Females and AIE exposed rats showed more conditioned lever presses (sign‐tracking), whereas AIE exposure significantly decreased conditioned receptacle entries (goal‐tracking). Collectively, our findings suggest that females are more susceptible to cue sensitivity after repeated consumption of EtOH during adolescence.